PENGARUH METODE WAFA TERHADAP KEMAMPUAN ANAK MEMBACA AL-QURâ€™AN DI MI AL-HIDAYAH MANGKUJAJAR KEMBANGBAHU LAMONGAN - Musa'adatul Fithriyah (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2019)
The Qur'an learning is very fundamental in Islamic education, especially in elementary education. The Qur'an is one of the subjects that must be taught to children. Early education in the Qur'an is expected to produce young people having a strong mental foundation, education not only makes children as prosperous in the world, but also provides sufficient provisions to both improve their religion and practice their scriptures. To be able to practice the Holy Qur'an correctly, children must be guided and taught how to read the Qur'an properly in accordance with the rules of true recitation. In fact the Qur'an learning at MI AL-Hidayah Mangkujajar Kembangbahu Lamongan initially tended to be monotonous for being dominated by conventional learning methods. As a result,Â  the Qur'an learning only produced generations that could read the Qur'an with the average ability without any sense of love and closeness to the Qur'an instead of having enthusiasm in learning it well. As time goes by, the Qur'an learning at MI Al-Hidayah has increasingly developed by applying the so-called Wafa method. This method teaches children to be able to read and memorize the Qur'an by maximizing the right brain. This is classified as a new method, but it is quite practical and fun in the learning process. The research was aimed at determining the effect of the Wafa method on the ability of children to read the Qur'an at MI Al-Hidayah Mangkujajar Kembangbahu Lamongan. The research method is quantitative with the experimental type of one group pretest-post test, data analysis techniques use the mean pretest and posttest, in addition, to testing the hypothesis it uses the Paired Sample T-Test with the SPSS 16. The results showed the influence of the Wafa method on the children ability to read the Qur'an at MI Al-Hidayah Mangkujajar Kembangbahu Lamongan. It was proven from the results of the analysis through the mean pretest formula, it was obtained a value of 82.92 and increased in the acquisition of the mean value of posttest amounted to 85.75. In addition, in the Paired Sample T-Test based on significance values with SPSS 16, it is known that the Sig. (2-tailed) value is 0,000 <0,05, because sig. (2-tailed) of 0,000 is smaller than 0.05, then the hypothesis is accepted and it could be concluded that there is an influence of the WAFA Method on the ability to read the Qur'an at MI Al-Hidayah Mangkujajar Kembangbahu Lamongan.